The diversity of movement patterns in the execution of a «Top spin» right-handed stroke in table tennis among elite athletes - Barchukova G.V.; Vagin A.Yu.; Qian Daoming (Theory and Practice of Physical Culture, 2025)
Objective of the study was to investigating the fluctuations in the motion patterns of the «top spin» forehand stroke in table tennis among elite players. Methods and structure of the study. Eight expert male table tennis players executed a «top spin» on the right side of the ball under standard circumstances, adjusting the speed and power to perfection, aiming to strike the ball in a specific area of the table. Each athlete attempted to execute the «top spin» at least five times. The spatial and temporal motion parameters were recorded using the Qualisys hardware and software system. The Qualisys Track Manager software was employed to initially gather data from six high-speed ProReflex video cameras during the biomechanical analysis. The shooting frequency in the experiment was set at 200 Hz. Results and conclusions. Based on the analysis of the trajectory and velocity of the racket, we determined the following kinematic parameters of the «top spin» forehand: - The maximum velocity of the racket. - The duration of each of the three selected phases of the «top spin» stroke. - The path of the racket during each of the three selected phases of the stroke. The obtained kinematic parameters of the «top spin» forehand for eight tennis players, along with their average values and coefficients of variation, reflect the significant differences in technique among individuals. It is possible that tennis players employ distinct approaches to accelerate the striking arm when executing the top spin forehand.